2002
DOI: 10.1046/j.1420-9101.2002.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in plumage colour among birds: species recognition or light environment?

Abstract: The traditional explanation for interspecific plumage colour variation in birds is that colour differences between species are adaptations to minimize the risk of hybridization. Under this explanation, colour differences between closely related species of birds represent reproductive character displacement. An alternative explanation is that interspecific variation in plumage colour is an adaptive response to variation in light environments across habitats. Under this explanation, differences in colour between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 46 publications
10
139
3
1
Order By: Relevance
“…This conclusion necessarily implies that the signal environment has had an important influence on signal design in the Pipridae (Endler and Théry 1996;Heindl andWinkler 2003a, 2003b;Uy and Endler 2004), and other studies suggest that this may be a widespread pattern in birds (McNaught and Owens 2002;Gomez and Théry 2004). We also show that plumage colors produced by particular mechanisms may optimize either efficacy or content and may be more effective signals at particular viewing distances.…”
Section: Multiple Benefits Of Multiple Patchessupporting
confidence: 67%
See 1 more Smart Citation
“…This conclusion necessarily implies that the signal environment has had an important influence on signal design in the Pipridae (Endler and Théry 1996;Heindl andWinkler 2003a, 2003b;Uy and Endler 2004), and other studies suggest that this may be a widespread pattern in birds (McNaught and Owens 2002;Gomez and Théry 2004). We also show that plumage colors produced by particular mechanisms may optimize either efficacy or content and may be more effective signals at particular viewing distances.…”
Section: Multiple Benefits Of Multiple Patchessupporting
confidence: 67%
“…We were unable to take into account such species-specific modification of the display environment in our analyses, which suggests that the patterns we document here are quite general and may even underestimate of the strength of selection for signal efficacy in manakin plumage ornaments. Moreover, support from other comparative studies suggests that the visual environment may have a widespread influence on ornamental plumage coloration in birds (McNaught and Owens 2002;Gomez and Théry 2004).…”
Section: Selection For Signal Efficacymentioning
confidence: 68%
“…However, the selective forces driving UV evolution are beyond the scope of this study. Light environment most probably plays a role in the evolution of colour patterns (Endler & Théry 1996;Fuller 2002;McNaught & Owens 2002), as do other aspects of a given species biology. Hausmann et al (2003) concluded that UV coloration in Australian birds is associated with those areas of the plumage involved in courtship displays.…”
Section: Discussionmentioning
confidence: 99%
“…Using plumage brightness and hue, McNaught & Owens (2002) found that interspecific variation in plumage colour among six avian families responds to natural selection pressures acting on the signaling capacity of species. Thus, species living in closed habitats tend to present plumage mainly reflecting long-wavelength light (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…higher hue values) in order to increase chromatic contrast against surrounding vegetation. Conversely, species living in open habitats have brighter plumage more apt to signal over long distances (McNaught & Owens 2002). Gómez & Théry (2004) also concluded that ambient light is the best predictor of interspecific variation in plumage colour in 22 families of tropical birds.…”
Section: Introductionmentioning
confidence: 99%